Medically unexplained physical symptoms in emergency medicine. - Stephenson, D; Price, J (2006)
Medically unexplained physical symptoms (MUPS) are physical symptoms for which no relevant organic pathology can be found. Patients with MUPS commonly present to the emergency department (ED) but are rarely considered in emergency medicine teaching or literature. Management of these patients is frequently more challenging than where there is an obvious organic pathology. This review provides the emergency physician with background knowledge regarding the classification and aetiology of MUPS. It then provides strategies for more effective management, such as exploring the contribution of psychosocial factors with patients, explaining negative test results, and providing reassurance and avoiding creating iatrogenic anxiety. Early recognition of the fact that symptoms may not result from organic disease and an appreciation of the role of psychosocial factors may improve outcomes by reducing unnecessary investigation and admission, and avoiding reinforcement that encourages further similar presentations and unhelpful coping mechanisms.